(untitled) (CAHIERS MAGELLANES-NS, 2024)
The present study addresses the effectiveness of Spiritual Silence practices on the cognition of participants diagnosed with mood disorders in a pre-post practice study for which purposive sampling on 100 affected individuals have been conducted. The Addenbrooke’s Cognitive Examination-III (English and Hindi) was administered before and after the end of 5-7 days retreat program. The result show that there has been significant changes post-practice with increase in fluency, visuospatial abilities, memory, attention and overall Cognitive functioning. The durability of the results have not been tested. However, the results show significant betterment of cognitive functioning post-Spiritual Silence practice, deeming it a veritable intervention tool of mood disorders.